Experimental Investigation and Modelling of the Incipient Fault of Low-Voltage XLPE Cables in Wet Environments - Chen Zeng; Yunhe Wang; Miaomiao Wu; Yanru Lei; Jing Yong; Xiaojing Wang (Applied Sciences)
The study of incipient faults due to insulation defects in cables is crucial for preventing electrical fires and ensuring personal safety. However, research on incipient faults in low-voltage cables remains relatively underexplored compared to that on medium-voltage cables. This paper focuses on low-voltage cross-linked polyethylene (XLPE) cables and investigates the changes in voltage and current caused by insulation defects in different wet conditions. The main findings are that the voltage applied to the cable with defective insulation shows sub-cycle disturbances that become more frequent. The current in the cable conductor shows a pulsed shape, coincident with the voltage disturbances. Over time, the sub-cycle disturbances gradually disappear, instead, the steady-state leakage current emerges. The wet conditions affect waveforms of the voltage/current disturbance and the frequency of occurrence. The findings provide detailed and unique characteristics of the voltage and current during the cable incipient fault, which are different from those of the incipient fault in the medium-voltage cables. The simulation and analysis support the experimental results. Based on the experimental results, a model is developed for further research on LV-cable incipient fault detection and protection.